Evaluacion del uso de melaza en dietas para cerdos en crecimiento y engorde - Escobar Carvajal, J.E.=700 1 Macias Mock, M.D.; Castillo, R.; Velez, M.
(Es, En)
ilus., 17 ref.
Keywords: CERDO; DIETA; MELAZA; CRECIMIENTO; ENGORDE; DESEMPEÑO ANIMAL; HONDURAS